The zircon record of the Sudbury impact crater and its implications for the early Earth - Kenny, Gavin (Trinity College (Dublin, Ireland). Department of Geology, 2016)
In the absence of widespread rocks older than 4.0 Ga, the earliest terrestrial material and the only direct evidence for the nature of the Earth's very early crust are tiny zircon crystals. The chemical compositions of these Hadean zircons have been used to infer the composition and petrogenesis of the original host rocks and in turn the composition of, and processes acting on, Earth's very early crust. One of the few other relative certainties regarding the early Earth is that it was subjected to intense bolide bombardment. However, despite this being a well-acknowledged fact, very little is known about the effects of impact-induced shock metamorphism and reprocessing on the trace element and stable isotope geochemistry of zircon. Additionally, our knowledge of new zircon which crystallises in impact melt sheets is also very limited. This thesis presents investigations into the geochemistry of newly formed as well as shock metamorphosed zircon from the best preserved and most accessible large impact crater on Earth - the subaqueous, 1.85 Ga Sudbury impact structure, Ontario, Canada - as an analogue for impact craters on the early Earth.
Embargo End Date: 2020-07-01
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin, 2016